Synthesis of minimal schemes of systems control of hydraulic and pneumatic drives - Cherkashenko, M. V. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The existing schemes of command apparatus are presented. Their analysis is carried out and the shortcomings are indicated. The scheme of a fundamentally new command apparatus is given, which can significantly reduce the number of its elements. The synthesis of the pneumatic control system of the foundry machine was carried out on the basis of the design approach proposed by M. Cherkashenko, which as a result led to a reduction in the devices by 3.5 times. A graph of operations of the pneumatic control system of the molding machine is constructed. A matrix of correspondences is obtained, which determines the correspondence between the signals that cause transitions and the complete input sets acting in the transitions. Analysis of the matrix of correspondences made it possible to identify and eliminate contradictory transitions. On the basis of the elongations, a system of equations describing the scheme of the control system is synthesized. Further, minimization is performed due to factorization and decomposition of equations, and obtaining equations in their final form. A diagram is presented pneumatic control system of the molding machine, consisting of a command apparatus containing three cells, five cylinders, two vibrators, six limit switches, a time relay and other devices. The circuit simultaneously uses the functional and logical capabilities of limit switches, the possibility of implementing the functions of three variables by distributors. Thus, the use of the proposed command apparatus, in contrast to the existing schemes of command apparatus, can significantly reduce the number of distributors in the synthesis of the command apparatus itself and significantly reduce the number of elements when using the chosen approach to the design of circuits of pneumohydraulic control systems.

Представлені існуючі схеми командоапарату. Проводиться їх аналіз і вказуються недоліки. Наведено схему принципово нового командоапарату, який дозволяє значно скоротити кількість його елементів. Синтез пневматичної системи управління ливарним верстатом здійснювався на основі конструктивного підходу, запропонованого М. Черкашенко, що в результаті призвело до скорочення пристроїв в 3,5 рази. Побудовано граф операцій пневматичної системи управління формувальної машини. Синтезована матриця відповідностей, яка визначає відповідність між сигналами, що викликають переходи, і повними вхідними множинами, що діють в переходах. Аналіз матриці відповідностей дозволив виявити і усунути суперечливі переходи. На основі подовжень синтезується система рівнянь, що описують схему системи управління. Далі виконується мінімізація за рахунок факторизації і розкладання рівнянь, і отримання рівнянь в їх кінцевому вигляді. Представлена схема пневматичної системи управління формувальної машини, що складається з командоапарату, що містить три осередки, п'ять циліндрів, два вібратори, шість кінцевих вимикачів, реле часу та інші пристрої. Схема одночасно використовує функціональні та логічні можливості кінцевих вимикачів, можливість реалізації розподільниками функцій трьох змінних. Таким чином, застосування запропонованого командоапарату, на відміну від існуючих схем командоапаратів, дозволяє значно скоротити кількість розподільників при синтезі самого командоапарату і значно зменшити кількість елементів при використанні обраного підходу до проектування схем пневмогідравлічних систем управління.
Синтез мінімальних схем систем управління гідро- і пневмоприводів
Keywords: mathematical model; graph of operations; minimal scheme; equations; matrix of correspondences; command apparatus; математична модель; граф операцiй; мінімальна схема; рівняння; матриця відповідностей; командоапарат